2002
DOI: 10.1007/s00586-002-0469-8
|View full text |Cite
|
Sign up to set email alerts
|

Complications of pedicle screws in lumbar and lumbosacral fusions in 105 consecutive primary operations

Abstract: Pedicle screw fixation is technically demanding and associated with high complication rates. The aim of this study was to identify and quantify the pedicle screw-related complications in 105 consecutive operations. We retrospectively analysed 105 consecutive primary operations. We found complications of varying severity in 54% of the patients. Deep infections were found in 4.7%, all successfully cured by debridement and antibiotics. There were no permanent neurological complications related to the screws. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
165
3
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(176 citation statements)
references
References 18 publications
4
165
3
4
Order By: Relevance
“…The failure rates ranged from 0.4 to 22% [10][11][12][13][14][15][16][17]. Interestingly, some characteristics of the implant failures in this study differed from those involving lumbar or thoracolumbar fusions reported in the literature.…”
Section: The Characteristics As For Cervical Instrumentation Failurementioning
confidence: 59%
See 1 more Smart Citation
“…The failure rates ranged from 0.4 to 22% [10][11][12][13][14][15][16][17]. Interestingly, some characteristics of the implant failures in this study differed from those involving lumbar or thoracolumbar fusions reported in the literature.…”
Section: The Characteristics As For Cervical Instrumentation Failurementioning
confidence: 59%
“…First is the lack of rod fractures. Jutte et al [16] reported a 0.9% incidence of rod failure in 105 lumbar or lumbosacral fusions, and in most other reports, rod fractures occurred after posterior lumbar fusion surgery. Intraoperative rod contouring and corrective procedures using reduction devices are generally thought to be risk factors for the failure of spinal constructs, particularly with pure titanium or titanium alloy implants because of their notch sensitivity [10,18,19].…”
Section: The Characteristics As For Cervical Instrumentation Failurementioning
confidence: 94%
“…Although several studies have shown satisfactory outcomes from spinal fusion for such spinal disorders, risks of complications associated with the extensive surgery remain, particularly in old patients [18,28,30]. In this context, development of less-invasive spinal fusion options is desirable to treat spinal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Screw misplacement may cause neurologic and vascular complications. Pedicle screw-related complications have been reported to range from 1 % up to 54 % [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%